FACE RECONSTRUCTION THROUGH LIPOSTRUCTURE - Cristian Drochioi; Victor Vlad Costan; Otilia Boisteanu; Eugenia Popescu (Romanian Society of Oral Rehabilitation, 2015)
Grafting adipose tissue to correct the soft parts in the maxillo-facial area was first used and described over 100 years ago by Neuber, in his search for an ideal natural material [1]. By sampling some block of adipose tissue from the abdomen, the author carried out a fine correction of volume flaws at the level of the cephalic extremity. In 1912, Hollander underlines and reports the facial modifications that appear after fat infiltration in the case of patients with facial lipoatrophy [2]. A step forward is taken in 1926 by Miller, who published data based on his own experience regarding fat injection, using his own cannulas [3]. This technique represented a huge step forward compared to the sampling of blocks of fat tissue, being somehow similar to the technique of lipostructure, the essential difference being that the sampled material was not centrifuged